TEORI DAN KONSEP PERLINDUNGAN ANAK DI INDONESIA - S, Laurensius Arliman (Ensiklopedia of Journal, 2024)
Abstrak: The theory of child protection focuses on efforts to ensure the well-being and fundamental rights of children are adequately safeguarded in social, economic, political, and cultural life. In the context of Indonesia, a child is defined as any individual who has not reached the age considered as adulthood under Indonesian positive law, whether married or not. Child protection in Indonesia is regulated by various laws, including the Law on Child Protection, which provides the legal basis for fulfilling children's rights and protecting them from all forms of violence, exploitation, discrimination, and harmful treatment. The concept of legal protection for children includes prevention, recovery, and rehabilitation, as well as efforts to ensure children's safe participation in various aspects of life. This study aims to examine the theory and concept of child protection in Indonesia to strengthen the legal system that proactively safeguards children from all threats and violations.Keywords: Theory, Concept, Child Protection.